B cell depletion therapy for patients with systemic lupus erythaematosus results in a significant drop in anticardiolipin antibody titres. Issue 3 (28th September 2007) - Ioannou, Y; Lambrianides, A; Cambridge, G; Leandro, M J; Edwards, J C W; Isenberg, D A
Abstract : Background: B cell depletion therapy (BCDT) has recently been used with success to treat patients with rheumatoid arthritis and systemic lupus erythematosus (SLE). As antiphospholipid antibodies have been implicated in the pathogenesis of the antiphospholipid syndrome (APS), we asked the question whether BCDT affects levels of IgG anticardiolipin antibodies (aCL) in our cohort of 32 SLE patients given this treatment. Methods: We identified seven SLE patients who had undergone BCDT and had had at least two moderate positive aCL titres at least 12 weeks apart. Of these only one patient had APS. IgG aCL were measured at time 0 and 6–9 months post BCDT. Results: At time 0, the mean IgG aCL level was 20.6 standardized IgG antiphospholipid units (GPLU) (range (SD) 10–32, (10.1), normal level <5). At 6–9 months post depletion the IgG aCL levels in six of the seven patients was undetectable and in the other patient the level reduced from 25 GPLU to 15 GPLU (p<0.005, two-tailed paired t test). At baseline, only one patient had a mildly positive anti-β2 -glycoprotein I (β2 GPI) antibody level at 30% (compared to an in-house standard), which fell to 5% post-BCDT. Conclusions: This small observational study in patients with SLE is the first to demonstrate that BCDT results in a significant reduction in levels of IgG aCL.